Uric acid - its role as a risk factor for the metabolic syndrome, cardiovascular and kidney disease - Storhaug, Hilde (UiT The Arctic University of Norway, 2016)
Uric acid as a potential risk factor for cardiovascular and renal conditions has gained renewed attention. In this work we aimed to assess the associations between serum uric acid, metabolic syndrome, hypertension, renal dysfunction, cardiovascular events and mortality. In paper I, 6083 participants from Tromsø 4 were stratified according to body mass index. Endpoints were the metabolic syndrome and each component of the syndrome after seven years. Increased levels of baseline serum uric acid independently predicted development of hypertension and higher fasting glycemia in the overweight, but not in the normal-weight subjects. Baseline and longitudinal serum uric acid were both predictors of future metabolic syndrome. A prospective study that included 2637 participants who participated in Tromsø 4, 5 and 6 was described in paper II. We assessed the associations between change in serum uric acid during follow-up, baseline serum uric acid and renal dysfunction (defined as albumin-creatinine-ratio ≥1.13 mg albumin/mmol creatinine and/or estimated glomerular filtration rate < 60 ml/min/1.73 m2). Participants were stratified according to tertiles of change in serum uric acid between baseline and follow-up 13 years later. The upper tertile, compared to the two lower tertiles, had a doubled risk of renal dysfunction after 7 years, and after 13 years the odds ratio for renal dysfunction was 2.18. The risk of developing albumin-creatinine-ratio ≥1.13 mg/mmol alone was also significantly increased. An increase in baseline serum uric acid of 59 μmol/L gave an odds ratio of 1.16 for renal dysfunction after 13 years. In paper III, we included 5700 participants from Tromsø 4, and assessed the associations between serum uric acid and all-cause mortality after 15 years, and fatal or non-fatal myocardial infarction and ischemic stroke after 12 years. Serum uric acid was associated with all-cause mortality in men and women, even after adjustment for blood pressure, estimated glomerular filtration rate, urinary albumin ...